Characterization of the physicochemical, bromatological properties, and antioxidant activity of powdered sugarcane bagasse - Cabrera, Alanís; Velásquez, Maritza; Muñoz , José (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
By-products are currently considered important foods for human consumption due to their large contribution of bioactive compounds. The objective of the study was to characterize the physicochemical, bromatological, and antioxidant properties of powdered sugarcane bagasse. To obtain sugarcane bagasse powder (PBCA), samples were collected in three artisanal sugar mills in the Junín canton, province of Manabí. The samples were labeled under the codes; M1, M2, and M3. An analysis of variance and Tukey's test at 5 % significance were applied. Statistical significance was determined between the samples evaluated, the results demonstrated a variation in the physicochemical properties: pH (5.96 ± 0.01 – 7.14 ± 0.05); acidity (0.09 ± 0.00 – 0.37 ± 0.00 %); moisture (5.05 ± 0.32 – 9.80 ± 0.68 %) and ash (1.94 ± 0.00 – 4.47 ± 0.02 %), bromatological: crude fiber (13.85 ± 0.11 – 24.39%); protein (0.16 ± 0.00 – 0.86 ± 0.01 %); dry matter (88.52 ± 3.51 – 94.94 ± 0.32%) and fat (0.09 ± 0.00 – 0.13 ± 0.01%), functional and antioxidant compounds: hemicellulose (25.32 ± 0.79 %); cellulose (17.90 ± 0.05 – 26.83 ± 0.20%); lignin (0.31 ± 0.00 – 0.51 ± 0.00 %); water retention capacity (3.27 ± 0.01 – 4.93 ± 0.19 g H2O.g-1); antioxidant activity (3.70 ± 0.03 – 9.92 ± 9.12 µmol trolox equivalent.g-1) and total phenols (2.19 ± 0.00 – 13.35 ± 0.03 mg gallic acid equivalent.g-1). All samples were microbiologically acceptable. PBCA presented nutritional characteristics of importance for the formulation of products for human consumption.